Assessment of a screening protocol for type 2 diabetes in community pharmacy. The DiabNow Study - Fikri-Benbrahim, N.; Martínez-Martínez, F.; Saéz-Benito, L.; Luque, B.; Corpas, J.; Moullin, Joanna; Sabater-Hernández, D. (Elsevier Ireland Ltd, 2015)
© 2015 Elsevier Ireland Ltd. The aim of this study was to assess the performance and feasibility of a protocol for screening type 2 diabetes in community pharmacy. Performance was primarily assessed by measuring stakeholders' adherence (pharmacists, patients and physicians) to the protocol's components.